Aprendizagem de frações por meio de jogos no 6º ano do ensino fundamental - CARNEIRO, Irisnan Antônia dos Santos (2025)
This study aims to analyze the effects of the use of games on the teaching and learning of fractions in a 6th grade class of a municipal public school in the community of Abade in the municipality of Curuçá-Pará. To this end, theoretical studies were carried out based mainly on authors who discuss the subject, in order to know the main learning difficulties, so that, later, the intervention in reality. The intervention process occurred, firstly, through diagnostic tests to verify the difficulties, when it was found that part of these difficulties result from the difference established between daily use and the way they are taught at school and, specifically in the field of work with fractions, the identification of numerator and denominator would be the most immediate difficulty. Based on these findings, the process of pedagogical intervention through games was considered. It is considered important to use games in fraction teaching, as they allow content previously taught in a merely theoretical way to be seen in practical actions and compared to everyday elements. The "Domino of fractions" proved to be efficient in overcoming the difficulties encountered.